Neoantigen-specific CD4+ T-cell response is critical for the therapeutic efficacy of cryo-thermal therapy - Ping Liu; Peng Peng; Hongming Hu; Lisa X Xu (Journal for ImmunoTherapy of Cancer)
Background Traditional tumor thermal ablations, such as radiofrequency ablation (RFA) and cryoablation, can result in good local control of tumor, but traditional tumor thermal ablations are limited by poor long-term survival due to the failure of control of distal metastasis. Our previous studies developed a novel cryo-thermal therapy to treat the B16F10 melanoma mouse model. Long-term survival and T-cell-mediated durable antitumor immunity were achieved after cryo-thermal therapy, but whether tumor antigen-specific T-cells were augmented by cryo-thermal therapy was not determined.Methods The long-term antitumor therapeutic efficacy of cryo-thermal therapy was performed in B16F10 murine melanoma models. Splenocytes derived from mice treated with RFA or cryo-thermal therapy were coincubated with tumor antigen peptides to detect the frequency of antigen specific CD4+ and CD8+ T-cells by flow cytometry. Splenocytes were then stimulated and expanded by αCD3 or peptides and adoptive T-cell therapy experiments were performed to identify the antitumor efficacy of T-cells induced by RFA and cryo-thermal therapy. Naïve mice and tumor-bearing mice were used as control groups.Results Local cryo-thermal therapy generated a stronger systematic antitumor immune response than RFA and a long-lasting antitumor immunity that protected against tumor rechallenge. In vitro studies showed that the antigen-specific CD8+ T-cell response was induced by both cryo-thermal therapy and RFA, but the strong neoantigen-specific CD4+ T-cell response was only induced by cryo-thermal therapy. Cryo-thermal therapy-induced strong antitumor immune response was mainly mediated by CD4+ T-cells, particularly neoantigen-specific CD4+ T-cells.Conclusion Cryo-thermal therapy induced a stronger and broader antigen-specific memory T-cells. Specifically, cryo-thermal therapy, but not RFA, led to a strong neoantigen-specific CD4+ T-cell response that mediated the resistance to tumor challenge.